Religious ideas in the national concepts in the Balkans - Paszkiewicz, Jędrzej; Szulc, Witold (Balcanica Posnaniensia. Acta et studia, 2010)
The article addresses the issue of the relationship between religion and nation-building processes in South-Eastern Europe. The background of the study is the centuries-old cultural and confessional mosaic of the Balkans, shaped at the intersection of Eastern Christianity, Western Christianity, and Islam. The authors analyze how religious diversity influenced the formation of national consciousness among Balkan communities from the nineteenth century to the present day. The aim of the study is to demonstrate that religion-despite processes of secularization and modernization – remained a key factor in integrating and legitimizing national ideologies. The authors particularly emphasize the role of autocephalous churches in Orthodox countries, which supported the development of state structures, civic attitudes, and the strengthening of national identity. The article is based on a comparative analysis of historical sources and scholarly works by European and Balkan researchers in the fields of intellectual history, cultural anthropology, and political science. The authors conclude that nation-building processes in the Balkans required a compromise between traditional religious values and modern political ideas derived from the West. Religion functioned both as a factor of integration and as a tool of political instrumentalization, used to legitimize borders, territorial claims, and ethnic distinctiveness. Although the influence of religion on national consciousness varied depending on context - Orthodox, Catholic, or Islamic domination – it remained a crucial component of collective identity and a lasting factor of the cultural diversity of the Balkans.